JURIDICAL REVIEW OF LEGAL PROBLEMS IN E-COMMERCE - Himawan, Oei Leonardo; Sulaksono, Agam; Suyatno, Suyatno (PT. Altin Riset Publishing, 2025)
Electronic commerce does provide many benefits, but it is also prone to violations of consumer rights. Law No. 19 of 2016 concerning ITE, Law No. 7 of 2014 concerning Trade and Law No. 8 of 1999 concerning Consumer Protection have indeed been prepared by the Government to deal with this matter in theory but not in practice where complications arise such as the viral case of ordering tiles worth 28.7 million consumers losing money and not getting their orders. The purpose of writing this law is to find out the position and responsibilities of the Dropshipper if there is a violation of Consumer Rights, and what regulations need to be applied by the Government to Dropshippers as e-commerce service providers in electronic trade transactions. The use of a normative perspective legislative approach aims to explain the legal position in online trade transactions. This study investigates legal principles, legal systematics, the degree of legal synchronization, and legal history. The data used are from secondary, primary, and tertiary legal sources. The result of this writing research is that legal certainty can be answered with preventive steps, namely recording the identity of e-commerce platform actors who are required to have a business license based on Article 15 of PP PMSE. As well as the need for the role of the Ministry of Communication and Information to strive to supervise business actors in e-commerce.